Diagnosis and treatment of biaxial keratomas in the left fore foot of a 15‐year‐old Clydesdale mare. (7th August 2014) - Rowland, A. L.; Goodrich, L. R.; Bass, L. D.; Aldrich, E. D.; Edmondson, E. F.; Mueller, L. W.
Summary: A 15‐year‐old Clydesdale mare presented for further diagnostics and treatment of waxing and waning lameness and recurrent subsolar abscesses. Radiographs and computed tomography revealed biaxial masses extending from the hoof capsule, causing bone resorption of the distal phalanx. Surgery was performed to remove the masses and post operative care included regional limb perfusions, systemic antibiotics and therapeutic shoeing. Histopathology was consistent with the diagnosis of keratoma for each of the masses; this is the first case of confirmed biaxial keratomas. Two months after surgery the horse is sound at the walk and is expected to return to full function within the next year.